Vitamin C Consumption Affects the Treatment Period of Covid-19 Patients at Dr. Pirngadi Regional General Hospital - Mahardika, Virani; Syafina, Ikhfana; Hapsah, Hapsah; Arbaningsih, Sri Rezeki (Universitas Muhammadiyah Sumatera Utara, 2025)
Abstract: Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) or what we now know as Coronavirus disease (COVID-19) is a viral infection that has hit the world in the last three years. The management of patients confirmed with COVID-19 continues to be researched. Vitamin C is one of the therapies that can be given to COVID-19 patients from mild to severe or critical degrees. Vitamin C is an antioxidant whose function can reduce oxidative inflammation and greatly affect the human immune system. The dose of vitamin C administration in COVID-19 patients can be given up to high doses. Due to the protective properties of vitamin C, it can affect the treatment period of COVID-19 patients. This study aims to determine the relationship between vitamin C consumption and the length of treatment of COVID-19 patients at DR Pirngadi General Hospital. This study is an observational analytical study with a cross-sectional design. A total of 66 samples were obtained divided into low and high doses of vitamin C which were then analyzed using Chi Square. The results of the study found that there was a significant result (P=0.039) in the relationship between vitamin C consumption and the treatment period of COVID-19 patients. Vitamin C consumption affects the treatment period.